Chapter 62 Doing fieldwork on the body, language, and communication. - Enfield, N. J. (De Gruyter, 2013)
This chapter gives a brief and selective overview of how to approach research on bodilyand linguistic aspects of communication by doing fieldwork. Here I do not address tech-nological issues such as specific choices of video recording equipment or computerprograms for processing and analysis. Any such discussion would either be too pur-pose-specific or would quickly become obsolete due to the fast-moving nature of thetechnology. Our interest here is the general approach.